Evaluation of diagnostic efficacy of hepatobiliary scintigraphy as a diagnostic procedure in pediatric practice with special reference to cholestatic jaundice - Singh, D. K.; Yadav, Rajesh Kumar; Singh, Mukesh Veer; Singh, Mamta; Hazra, D. K.; Singh, Meena (International Journal of Research in Medical Sciences, 2017)
Background: The objective was to assess the diagnostic efficacy of hepatobiliary scintigraphy (Tc99 mebrofenin) in case of cholestatic jaundice in pediatric practice. Method: Study conducted on 45 cases from 0-6 yrs. of age. Out of 45 pt 20 pt excluded from study Hepatobiliary Scintigraphy (Tc99m Mebrofinin) was performed in 25 cases. Injection of Tc99m mebrofinin (1-2 mCi) IV was given to each subject. Dynamic hepatic scan was done upto initial 1 hour study and additional delayed images were taken at 4 & 24 hrs only in case of non-visualization of tracer in the intestine after initial 1 hr. study. Results: In this study hepatobiliary scintigraphy was 100% sensitive, 93.73% specific, 80% positive predictive values, 100% negative predictive value, 6.23% false positive result and virtually no false negative result for biliary atresia. Conclusion: It is concluded that Tc99m mebrofenin hepatobiliary scintigraphy has proven to be reliable noninvasive imaging modality in evaluating cholestatic jaundice in pediatric practice as it carries a high sensitive & specific value, good positive & no negative predictive value, few false positive & virtually no false negative results.